บทบาทสตรีในการดำเนินงานกองทุนหมู่บ้านและชุมชนเมือง ในเขตองค์การบริหารส่วนตำบลบุ่งคล้า อำเภอเมืองชัยภูมิ จังหวัดชัยภูมิ - กล้าประจันทร์ , มาลัย (Journal of Graduate MCU KhonKaen Campus, 2016)
การศึกษาครั้งนี้มีวัตถุประสงค์เพื่อศึกษาบทบาทของสตรีในการดำเนินงานกองทุนหมู่บ้านและชุมชนเมืองในเขตองค์การบริหารส่วนตำบลบุ่งคล้า อำเภอเมืองชัยภูมิ จังหวัดชัยภูมิ และเพื่อศึกษาปัญหาอุปสรรคแนวทางในการแก้ไขปัญหาและแนวทางในการส่งเสริมบทบาทสตรีในการดำเนินงานกองทุนหมู่บ้านและชุมชนเมืองในเขตองค์การบริหารส่วนตำบลบุ่งคล้า อำเภอเมืองชัยภูมิ จังหวัดชัยภูมิ กลุ่มตัวอย่างที่ใช้ในการศึกษา คือ สตรีที่ได้รับการคัดเลือกเป็นคณะกรรมการกองทุนหมู่และชุมชนเมือง จำนวน 12 กองทุน รวม 71 คน เครื่องมือที่ใช้ในการศึกษาครั้งนี้ เป็นแบบสัมภาษณ์แบบมีโครงสร้าง (Structured Interview) และแบบแนวทางการสนทนากลุ่ม (Focus Group) แล้วนำข้อมูลมาวิเคราะห์เนื้อหา(Content Analysis) พร้อมเสนอผลการศึกษาในรูปของความเรียง ผลการศึกษาบทบาทของสตรีในการดำเนินงานกองทุนหมู่บ้านและชุมชนเมืองในเขตองค์การบริหารส่วนตำบลบุ่งคล้า อำเภอเมืองชัยภูมิ จังหวัดชัยภูมิ ด้านบริหารจัดการกองทุน พบว่า คณะกรรมการยังขาดความรู้ความเข้าใจในการบริหารจัดการกองทุนและสมาชิกไม่ชำระเงินคืนตามสัญญา พร้อมทั้งเงินทุนหมุนเวียนไม่เพียงพอต่อความต้องการของสมาชิก ควรมีการฝึกอบรมให้สตรีมีความรู้ความสามารถและเป็นต้นแบบในการพัฒนาตนเองที่เอื้อต่อการบริหารจัดการกองทุน ด้านการออกระเบียบข้อบังคับ พบว่า สมาชิกไม่มีวินัย และไม่ปฏิบัติตามกฎระเบียบข้อบังคับของกองทุนที่กำหนดไว้ คณะกรรมการและสมาชิกกองทุนควรศึกษาระเบียบข้อบังคับให้เข้าใจและปฏิบัติตามกฎระเบียบที่กองทุนได้กำหนดไว้เพื่อให้กองทุนมีขีดความสามารถในการจัดระบบและบริหารจัดการเงินกองทุนของตนเอง ด้านการรับสมัครสมาชิกและการจัดทำทะเบียนสมาชิก พบว่า สตรีมีภาระงานบ้านและดูแลครอบครัว ควรมีการกระจายการทำงานให้คณะกรรมการปฏิบัติงานแทนกันได้และส่งเสริมให้เข้ารับอบรมเพื่อให้มีความรู้ในการนำเทคโนโลยีสารสนเทศมาประยุกต์ใช้ในการสืบค้นข้อมูล ด้านการส่งเสริมอาชีพ พบว่า สมาชิกกองทุนฯ ที่กู้ยืมเงินไปแล้วนำเงินกู้ไปใช้ผิดวัตถุประสงค์ของกองทุนฯ ไม่นำเงินไปใช้เพื่อการประกอบอาชีพของตนเองควรปลูกจิตสำนึกให้คนในชุมชนรู้จักการนำเงินที่กู้ยืมไปใช้เพื่อการประกอบอาชีพของตนเองและส่งเสริมให้สตรีมีบทบาทในการเข้าไปให้คำแนะนำในการส่งเสริมกลุ่มอาชีพใหม่ๆ ด้านการพิจารณาเงินกู้ พบว่า คณะกรรมการกับสมาชิกกองทุนฯ มีความขัดแย้งกันในเรื่องพิจารณาเงินกู้ กล่าวหากรรมการไม่มีความโปร่งใสในการทำงาน ควรประชุมสมาชิกเพื่อชี้แจง วิธีการ หลักเกณฑ์ ในการพิจารณาอนุมัติเงินกู้ให้สมาชิกเข้าใจ ด้านการประชุม พบว่า สมาชิกกองทุนฯไม่ให้ความร่วมมือมาประชุมโดยเฉพาะสมาชิกที่กู้เงินไปแล้วกลัวที่ประชุมทวงให้ชำระหนี้ ควรมีกฎเหล็กของหมู่บ้านบังคับใช้ให้สมาชิกมีส่วนร่วมในการประชุมเพื่อทราบข้อมูลข่าวสารและความเคลื่อนไหวของกองทุนหมู่บ้านของตนเอง ด้านการจัดทำบัญชี พบว่า การลงบัญชีไม่เป็นปัจจุบัน ยังขาดความรู้ด้านบัญชีทำให้การบันทึกบัญชีเกิดความผิดพลาดระบบบัญชีจึงไม่ต่อเนื่อง ควรคัดเลือกกรรมการกองทุนที่มีพื้นฐานความรู้ทางด้านบัญชีมอบหมายและส่งเสริมให้มีบทบาทในด้านการจัดทำบัญชีลงบัญชีให้เป็นปัจจุบัน เพราะบัญชีจะเป็นเครื่องมือในการวัดผลการดำเนินงานและแสดงฐานะทางการเงินที่แท้จริงของแต่ละกองทุน The objective of this independent study were to study the Woman’s role in operation of Village Fund and urban area, problems and limitations, an approach to solve the problems, and an approach to support woman’s role in operation of Village Fund and urban area of Bungkla Subdistrict Administration, Mueng district, Chaiyaphum Province. The samples were the women who were elected to be the committees of Village Fund and urban area amount 12 Funds tootled 71 persons. The methods of collecting data were Structured Interview and Focus Group Discussion, analyzing by Content Analysis and presenting by composition. The seven issues of problems and limitations, an approach to solve the problems, and an approach to support woman’s role in operation of Village Fund and urban area showed that, the administration of funds found the committee lacked the knowledge in funds administration, the members did no pay money back according to the contract, so that made the funds could not suffice for the members need, therefore the woman were trained to get the capability to be the model in developing oneself that affected to the administration of funds. The legislation found the members were not orderly and did not followed the rules of funds and the committees and members should studied the rules and followed the rules to get the capability in administration of the funds system. The admission and registration of the members found the woman had housework and took care the family so they had no times for this reason there was give out to the committees and giving the knowledge about technology to apply in searching the data. The supporting the occupation found some of members borrowed money in the wrong way, spent money to satisfy the needs that did not earn a living, so we should making a conscious to the villagers to use the money in developing the occupation and supporting the woman’ roles to suggest the new occupation. The examining the loan found the committees and members had a conflict in examining the loan those members accused the committees did not reveal in working, took care only own partisan, so they should had meeting to explain the method in examining the loan to members to get understand. The conference found some of members did not participate the meeting especially the members who borrowed money that they afraid of the committees demanded payment of a debt, although there were the document to call before meeting, there also had the iron rule effort them to participate the meeting to know the data and the movement of funds. The making account found there was no update that lacked the knowledge to making account effect to made a mistake, the account system did not continued, so there was choose the committees who had a basic knowledge of accounting and supporting the women got the knowledge and competency in making accounting to be presently because the accounting will be the measuring instrument and showing the financial status of each funds actually.